2006
DOI: 10.1111/j.1075-122x.2006.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled, Crossover Study of Sertraline (Zoloft) for the Treatment of Hot Flashes in Women with Early Stage Breast Cancer Taking Tamoxifen

Abstract: We observed the relief of hot flashes in breast cancer survivors taking tamoxifen and treated with sertraline for depression. Our objective was to assess the effect of sertraline on the frequency and severity of hot flashes, mood status, and health-related quality of life. We used a randomized, double-blind, placebo-controlled, crossover study using 6 weeks of sertraline (50 mg each morning) versus placebo. Study participants were 62 breast cancer survivors from an oncology clinic in a tertiary care center on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 35 publications
1
73
0
5
Order By: Relevance
“…The selective serotonin reuptake inhibitor (SSRI) and selective serotonin-norepinephrine reuptake inhibitor (SSNRI) antidepressant classes have been used successfully to reduce the frequency and severity of vasomotor symptoms associated with breast cancer and tamoxifen use. [40][41][42][43] It is therefore possible that concomitant use of tamoxifen and certain SSRIs/SNRIs could improve tamoxifen persistence by minimizing side effects. Whether women continued with or commenced antidepressant use after initiation of tamoxifen was not recorded for this study and as a result it is not possible to draw conclusions about the effect of concurrent antidepressant use on tamoxifen persistence.…”
Section: Discussionmentioning
confidence: 99%
“…The selective serotonin reuptake inhibitor (SSRI) and selective serotonin-norepinephrine reuptake inhibitor (SSNRI) antidepressant classes have been used successfully to reduce the frequency and severity of vasomotor symptoms associated with breast cancer and tamoxifen use. [40][41][42][43] It is therefore possible that concomitant use of tamoxifen and certain SSRIs/SNRIs could improve tamoxifen persistence by minimizing side effects. Whether women continued with or commenced antidepressant use after initiation of tamoxifen was not recorded for this study and as a result it is not possible to draw conclusions about the effect of concurrent antidepressant use on tamoxifen persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies were largely undertaken in breast cancer survivors, and the number and severity of VMS were less than the standards required by the US Food and Drug Administration (FDA) and utilized in randomized controlled studies of hormone therapies [32][33][34][35][36]. Efficacy in reducing the number and severity of VMS averages around 65% with SSRIs like fluoxetine (20 mg/d) and paroxetine (12.5-25 mg/d), and an SNRI like venlafaxine (37.5-75 mg/d).…”
Section: Ssris and Snrismentioning
confidence: 99%
“…11 Findings from pilot trials of 2 other newer antidepressants, mirtazapine and citalopram, suggested that they also are efficacious and well tolerated. 27,28 Nonetheless, significant efficacy was not reported in a recent trial that looked for long-term effects of fluoxetine and citalopram, compared with placebo, in 150 postmenopausal women with hot flashes.…”
Section: Newer Antidepressantsmentioning
confidence: 99%
“…There are several centrally acting compounds that have been investigated as a means of alleviating hot flashes in women ( Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Potential mechanisms for their efficacy have been described in detail. 15 The present article delineates the histories of several of these classes of agents in the order in which they were first investigated.…”
mentioning
confidence: 99%